Neurotoxicity-sparing radiotherapy for brain metastases in breast cancer: a narrative review - Buczek, Dagmara; Zaucha, Renata; Jassem, Jacek (Frontiers in Oncology, 2024)
Breast cancer brain metastasis (BCBM) has a devastating impact on patient survival, cognitive function and quality of life. Radiotherapy remains the standard management of BM but may result in considerable neurotoxicity. Herein, we describe the current knowledge on methods for reducing radiation-induced cognitive dysfunction in patients with BCBM. A better understanding of the biology and molecular underpinnings of BCBM, as well as more sophisticated prognostic models and individualized treatment approaches, have appeared to enable more effective neuroprotection. The therapeutic armamentarium has expanded from surgery and whole-brain radiotherapy to stereotactic radiosurgery, targeted therapies and immunotherapies, used sequentially or in combination. Advances in neuroimaging have allowed more accurate screening for intracranial metastases, precise targeting of intracranial lesions and the differentiation of the effects of treatment from disease progression. The availability of numerous treatment options for patients with BCBM and multidisciplinary approaches have led to personalized treatment and improved therapeutic outcomes. Ongoing studies may define the optimal sequencing of available and emerging treatment options for patients with BCBM.